Cyclic Contractions on -Metric Spaces - E. Karapınar; A. Yıldız-Ulus; İ. M. Erhan (Abstract and Applied Analysis)
Conditions for existence and uniqueness of fixed points of two types of cyclic contractions defined on -metric spaces are established and some illustrative examples are given. In addition, cyclic maps satisfying integral type contractive conditions are presented as applications.